DAKWAH MELALUI KONSELING INDIVIDU - Ahmad Putra (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2019)
This paper explains about presenting the values ??of da'wah through individual counseling whose purpose is to provide religious / Islamic nuanced solutions to a variety of problems that exist in human life. The method used by the author in this research is descriptive analysis method, in which the author presents data from several relevant opinions and tested through various sources and then analyzes them, so as to produce a more effective and relatively new alternative in da'wah, namely through individual counseling. Then preaching must be packaged in the right method, which must be actual, factual, and contextual. One approach to convey the message of preaching is through individual counseling activities. Da'wah through individual counseling has several characteristics, namely the formation of communication between counselor and client, oriented toward problem solving efforts, delivery of messages that have been programmed, and the targets and objectives set. In addition, propaganda through individual counseling has several characteristics, namely trying to raise awareness to internalize the values ??/ teachings of Islam in certain circles that are very specific and individual.